Development of an ultrasonic decellularization process for porcine oesophagus - Toh, Amoz Jin Kai (Nanyang Technological University, 2021)
In the pursuit for suitable oesophageal replacements after an esophagectomy procedure, medical science has turned to regenerative medicine, specifically the aspect of tissue engineering. Studies have proven thus far that these methods have produced bio-scaffolds that can be reconstructed to form oesophagi that will have better biocompatibility and bio-functionality, with a lessened risk of backlash of immune rejection by the recipient body. The best bio-scaffolds have been thus far obtained through the decellularizing of animal oesophagi, such as pigs and sheep. Through the use of 0.2% Sodium dodecyl sulphate (SDS) solution and the method of perfusion of about 147.5 µl/min, the processed oesophagi are often fully decellularized within 4 to 5 days to produce the scaffolds. However, it has been found that the process involved would often risk the contamination of the oesophageal specimens, especially if it is carried out over a long period of time. Therefore, it is of utmost importance that these bio-scaffolds are produced quickly and efficiently while keeping the optimal standard in mind. This project report is the study of the development of a prototype ultrasonic decellularization system that will provide the periodic emission of ultrasonic waves with a 40 kHz frequency. The objective of this system is to improve the efficiency of the decellularization of the porcine oesophagus. The report will also include the recommendations for improvements and possible future studies to further develop an optimal decellularization system.